RESEARCH ON VIBRATION CONTROL METHOD OF TRAIN PANTOGRAPH - GUO YanHong (Jixie qiangdu)
In this paper, the vibration control method of train pantograph is studied. A dynamic equation based on Newton’s second law is established for the two element pantograph model. Magneto rheological damper is used to control the contact force fluctuation of pantograph catenary. A variable universe fuzzy controller is adopted as the control algorithm. The simulation results show that with the increase of train speed, contact force fluctuation is more obvious, this paper studies the power control method of arch vibration compared with the traditional fuzzy control and passive control method under the action of the contact force is not the average coefficient. When the magneto rheological damper is installed between the upper frame and the bow head, the contact force between the frame and the lower frame is lower than that of the lower frame, and the contact force of the pantograph catenary fluctuates less.